Gambaran Komunikasi Pemberdayaan dalam Komunitas UMKM Kreatif Kota Bontang - Cahyo, Mixo Septian Dwi; Rohmah, Ainun Ni’matu (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
The large number of MSME players in Indonesia is inseparable from the challenges or problems that exist. The number of problems can be a challenge for MSME players both those who run their businesses individually and in communities. The Creative MSME Community is an association community of various MSME players in Guntung Village, Bontang City. The purpose of this research is to explain the description of empowerment communication in the Creative MSME Community. This research uses the theory of ACTORS empowerment communication studies, and uses case study research methods and qualitative approaches. The data collection techniques were through observation and interviews. The results showed that the management of Creative MSME Community has not effectively carried out the empowerment communication process to the members. The interaction process between administrators and members also does not reflect the optimal use of interpersonal communication, so there are difficulties in creating mutual understanding.